2015
DOI: 10.1063/1.4932358
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic droplet solitons in orthogonal spin valves

Abstract: We review the recent experimental advancements in the realization and understanding of magnetic droplet solitons generated by spin transfer torque in orthogonal nanocontact based spin torque nanooscillators (STNOs) fabricated on extended spin valves and spin valve nanowires. The magnetic droplets are detected and studied using the STNO microwave signal and its resistance, the latter both quasistatically and time-resolved. The droplet nucleation current is found to have a minimum at intermediate magnetic field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 59 publications
(69 reference statements)
1
26
0
Order By: Relevance
“…Droplet states can be inferred by measuring the dc resistance of the nanocontact-a reversal of the magnetization produces a change in the nanocontact resistance [22][23][24][25][26][27][28] . Further, the magnetization dynamics of droplets can be detected experimentally through the ac electrical resistance oscillations in the nanocontact [22][23][24][25]27,28 caused by the precessing magnetization in the droplet.…”
Section: Creation Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Droplet states can be inferred by measuring the dc resistance of the nanocontact-a reversal of the magnetization produces a change in the nanocontact resistance [22][23][24][25][26][27][28] . Further, the magnetization dynamics of droplets can be detected experimentally through the ac electrical resistance oscillations in the nanocontact [22][23][24][25]27,28 caused by the precessing magnetization in the droplet.…”
Section: Creation Processmentioning
confidence: 99%
“…Both droplet and DS exhibit magnetic bistability over considerable ranges of applied current and magnetic field [22][23][24][25][26][27][28]32,34 . We investigate here the conditions that produce the annihilation of the solitonic modes when a lower degree of spin transfer torque-a lower current-is applied.…”
Section: Stabilitymentioning
confidence: 99%
“…Then, differently from [8] (where the conditions in Assumption 1.1 are used for developing the IST theory for (1.2) exploiting the gauge equivalence to the nonlinear Schrödinger equation and by solving the corresponding Riemann-Hilbert problem), in our treatment the inverse scattering problem is formulated directly in terms of the Marchenko integral equations. They are obtained by using a new triangular representation of the Jost solutions (see Propositions 2.3 and 2.4 in Section 2) which differs substantially from the triangular representations in [56] and [61] (e.g., see formulae (13) and (17) in [61]). In fact, the triangular representations introduced in [56] and [61] (and used in the literature thereafter) feature the spectral parameter λ as a factor multiplying the integral of the kernels, and this results in a rather involuted computation of the asymptotic behaviour for large λ of the Jost solutions (and consequently also of the scattering data), requiring the equivalence between (1.2) and the nonlinear Schrödinger equation to be obtained (see [25]).…”
Section: A)mentioning
confidence: 99%
“…Dissipative magnetic droplet solitons (droplets hereafter) are nonlinear confined wave excitations consisting of partially reversed precessing spins that can be created in films with perpendicular magnetic anisotropy (PMA) through the local suppression of the magnetic damping [16]. Droplets have been experimentally created using the STT effect in nanocontacts to PMA films [17][18][19][20][21][22][23], and droplets are a particular case of STToscillators. Recently reported experiments have shown that the stability of these collective excitations is limited by the appearance of drift instabilities, which were attributed to the disorderlocal variations of the effective magnetic field [21,24].…”
Section: Introductionmentioning
confidence: 99%